1999
DOI: 10.1002/pen.11628
|View full text |Cite
|
Sign up to set email alerts
|

Fiber‐forming properties of polymer mixture melts and properties of fibers on their basis

Abstract: The fiber‐forming properties of the following polymer mixture melts have been investigated: polypropylene‐copolyamide (PP/CPA), polyoxymethylene‐copolyamide (POM/CPA), POM‐copolymer of ethylene and vinyl acetate (POM/EVAC), PP/EVAC, EVAC/CPA, and polypropylene‐polyvinylalcohol (PP/PVA). The capability of the polymer mixture melts to fiber‐form was estimated by degree of the polymer melt longitudinal deformation. It has been determined that the fiber‐forming properties of polymer mixture melts can be regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Melt spinning can be used to manufacture multifilament yarns instead of the non‐woven mats described in the following sections. [ 99, 100 ] These yarns are sent as raw materials to textile factories. Melt spinning uses a raised extruder supplying polymer to a spinneret.…”
Section: Manufacturing Of Micro/nano‐fibrillated Foamsmentioning
confidence: 99%
“…Melt spinning can be used to manufacture multifilament yarns instead of the non‐woven mats described in the following sections. [ 99, 100 ] These yarns are sent as raw materials to textile factories. Melt spinning uses a raised extruder supplying polymer to a spinneret.…”
Section: Manufacturing Of Micro/nano‐fibrillated Foamsmentioning
confidence: 99%
“…80 Other authors have examined bril formation in the converging die entrance and found droplet coalescence to occur there. 30,80,81 In brief, in the case of the present study, the combined effect of deformation and coalescence leads to brillation of the PA11 dispersed phase droplets in viscoelastic PLA matrix modied by the ( CE [.…”
Section: Morphology Of the Blends In The Extrudatementioning
confidence: 99%
“…The second step, of forming process (by extrusion or injection) shall be carried out under conditions of temperature, strain rate deformation and residence time which do not to alter, or minimize the alteration of, the brillar structure previously obtained. For this purpose, the forming temperature of the dispersed phase must be 30 C higher than that of the matrix. Thus, taking into account the constraints imposed on the one hand for obtaining the brillation of the dispersed phase during compounding and stretching and on the other hand for preserving the brillar structure during forming process, the number of polymers pairs suitable for these processes and showing an industrial interest is generally relatively limited.…”
mentioning
confidence: 99%
“…Tsebenko et al investigated the fiber forming properties of polymer blends consisting of polypropylene/co‐polyamide (PP/CPA), polyoxymethylene/co‐polyamide (POM/CPA), polyoxymethylene/co‐ethylene vinyl acetate (POM/EVAC), PP/EVAC, EVAC/CPA, and polypropylene/polyvinyl alcohol (PP/PVA) via capillary viscometer measurements . Their findings indicate that the fiber forming properties of the resultant polymer blends depend strongly on the miscibility of the polymers and interactions between the polymers . In a related study poly(lactic acid)/PVA (PLA/PVA) blends were prepared via melt blending at varying PLA:PVA blend ratios and molded into thin plates .…”
Section: Introductionmentioning
confidence: 99%